Epigenetics in Paediatric Gastroenterology, Hepatology, and Nutrition: Present Trends and Future Perspectives. Issue 4 (April 2016) - Zilbauer, Matthias; Zellos, Aglaia; Heuschkel, Robert; Gasparetto, Marco; Kraiczy, Judith; Postberg, Jan; Greco, Luigi; Auricchio, Renata; Galatola, Martina; Embleton, Nicholas; Wirth, Stefan; Jenke, Andreas
Abstract : ABSTRACT: Epigenetics can be defined as stable, potentially heritable changes in the cellular phenotype caused by mechanisms other than alterations to the underlying DNA sequence. As such, any observed phenotypic changes including organ development, aging, and the occurrence of disease could be driven by epigenetic mechanisms in the presence of stable cellular DNA sequences. Indeed, with the exception of rare mutations, the human genome-sequence has remained remarkably stable over the past centuries. In contrast, substantial changes to our environment as part of our modern life style have not only led to a significant reduction of certain infectious diseases but also seen the exponential increase in complex traits including obesity and multifactorial diseases such as autoimmune disorders. It is becoming increasingly clear that epigenetic mechanisms operate at the interface between the genetic code and our environment, and a large body of existing evidence supports the importance of environmental factors such as diet and nutrition, infections, and exposure to toxins on human health. This seems to be particularly the case during vulnerable periods of human development such as pregnancy and early life. Importantly, as the first point of contact for many of such environmental factors including nutrition, the digestive system is being increasingly linked to a number of "modern" pathologies. In this review article, we aim to give a brief introduction to the basic molecular principals of epigenetics and provide a concise summary of the existing evidence for the role of epigenetic mechanisms in gastrointestinal health and disease, hepatology, and nutrition.